Binary polyamide hybrid composites containing carbon allotropes and metal particles with radiofrequency shielding effect. (24th October 2018) - Oliveira, Filipa; Dencheva, Nadya; Lanceros‐Méndez, Senentxu; Nunes, Teresa; Denchev, Zlatan
Abstract : Novel hybrid composites with polyamide 6 (PA6) matrices and binary metal/carbon allotrope reinforcements are synthesized using a two‐stage method. First, activated anionic ring‐opening polymerization (AAROP) of ε‐caprolactam is performed in suspension, in the presence of the desired amounts of different metal particles (Al, Cu, Fe, or Mg) and carbon allotropes (multi‐walled carbon nanotubes or carbon black). The AAROP produces dual core PA6 microcapsules (PAMCs) with controlled shape and size and a total metal/carbon load of up to 17 wt% in respect to the PA6 matrix. Second, these PAMC are compression molded to composite plates. The morphology and the crystalline structure of the different PAMC and their respective composites are studied by electron microscopy and thermal methods. The well‐dispersed binary metal–carbon allotrope fillers in the PA6 matrix increase its electrical conductivity by seven to nine orders of magnitude. Simultaneously, up to ca. 60% increase of the Young's modulus of the hybrids is registered. An almost total disappearance of the PA6 resonance lines in some of the binary hybrids is registered by solid state NMR spectroscopy. The tunable combination of enhanced electrical conductivity and screening of radiofrequencies can be potentially useful in electromagnetic interference shielding or radar absorbing materials. POLYM. COMPOS., 40:E1338–E1352, 2019. © 2018 Society of Plastics Engineers